2211 - Matthew B. Hudson (Medicine & Science in Sports & Exercise, 2015)
Patient advocates offer lived experience that can shape research priorities, methods, and outcomes. Patient engagement contributes valuable resources to research, including meaningful additions to research design, definition of research priorities, and dissemination of outcomes. It is therefore critical that patients and patient advocates be part of the biomedical research process; which can be achieved by changing the perspective of patients as the recipients of research outcomes, to being partners in the process. Patient, clinician, and researcher interactions are particularly important in rare disease research, where little funding is allocated to each disease, making the definition of research priorities even more important. Here, we outline how patients can contribute to biomedical research and provide a step-by-step guide for patient engagement at scientific conferences.